ANALISIS STRATEGI PENGEMBANGAN BUDIDAYA RUMPUT LAUT (Eucheuma cottonii) DI KELURAHAN NIPAH-NIPAH, KECAMATAN PENAJAM KABUPATEN PENAJAM PASER UTARA - Abdul Hadi Bone; Baedah Baedah (Jurnal Magrobis, 2018)
The coastal and marine areas of North Penajam Paser Regency have the potential of very rich natural resources, one of which is seaweed. This study aims to determine the strategies used in the development of seaweed cultivation, especially in the area of Nipah-nipah Sub-district Penajat of North Paser district. This research was conducted in Penajam Coastal Zone of north Paser Regency starting from June to September 2017. The research method used field survey method by interviewing fishermen seaweed fisherman community and library searching. The analysis used is SWOT analysis conducted to know the strategy of development of seaweed in the future. This analysis is based on the logic that maximizes strength (Strennghs) and opportunities (Opprtunities, but simultaneously also minimizes Weaknesses and Treants.) The results show that there are four alternative strategies for the development of seaweed that can be recommended that is the SO strategy used is to take advantage of all the potential of sea owned to seaweed processing business, processing, applying appropriate methods, seeking greater market opportunities and utilize the source of family labor optimally, ST strategy used is to increase production by conducting seaweed cultivation on time and methods to avoid ais-ais disease and improve the knowledge and skills of seaweed farming at the farm level, WO Strategy used by increasing cooperation with research institutions and government to obtain disease resistant seeds, various capital sources increase ki nerja groups, WT Strategy that digunaka is utilizing government support and multiply follow counseling and or training seaweed finance. Keywords : Seaweed Cultivation, Penajam Coastal Zone, SWOT